Differences In Hemoglobin Levels In Infected Patients Salmonella Typhi With Salmonella Paratyphi Based On Antibody Titer - Laelin Hijriyani; Fihiruddin Fihiruddin; Iswari Pauzi; Ersandhi Resnhaleksmana (Poltekkes Kemenkes Mataram, 2026)
Salmonella typhi and Salmonella paratyphi cause the disease known as typhus abdominalis. The pathogenicity that distinguishes Salmonella typhi and Salmonella paratyphi comes from the virulent part of the bacterial capsule. Virulence factors are found on the surface of Salmonella typhi that are not found in Salmonella paratyphi. The toxic effect of Salmonella that suppresses the bone marrow and the presence of bleeding in the intestine can cause anemia, so a supporting examination is needed, one of which is the examination of Hemoglobin levels. The aimt of this study is knowing the difference of hemoglobin levels in patients infected with Salmonella typhi and Salmonella paratyphi based on antibody titer against H antigens: This study used Analytical Observational method with cross-sectional approach. Data obtained from typhoid fever patients from the examination of hemoglobin levels at Patut Patuh Patju Hospital as many as 96 people using secondary data.